Oral health seeking behaviors of adults in Nebbi District, Uganda: a community-based survey - Juliet Ocwia; Ronald Olum; Pamela Atim; Florence Laker; Jerom Okot; Senai Goitom Sereke; Joseph Baruch Baluku; Sarah Kiguli; Felix Bongomin (BMC, 2021)
Abstract Background Dental health is often neglected by the majority of the population and has contributed to the global burden of oral diseases. We assessed awareness, utilization and barriers to seeking oral health care among adults in Nebbi District, Uganda. Methods A community-based, cross sectional study was conducted in the central division, Nebbi District in Uganda among adults between the age of 18 years or older. An interviewer-administered, semi-structured questionnaire was used for data collection on socio-demographic characteristics, oral health awareness, oral health utilization, associated factors and barriers. Results A total of 400 adults with a median age of 32 years (interquartile range 24-43) years were enrolled. More than half (57.5%, n = 230) of the participants were female. Participants identified smoking (42.8%, n = 171) and consumption of sugary foodstuffs (29.0%, n = 116) as risk factors for oral disease. Not brushing was also identified by 260 participants (65.0%) as the cause of tooth decay and 95.8% (n = 383) believed brushing one's teeth could prevent tooth decay. Of the 51.5% (n = 206) who had experienced a toothache or discomfort 12 months prior to the study but only about half (52%, n = 106) had sought healthcare from a dental clinic or facility. About 89.5% (n = 94) of the participants were able to see a dentist during their last visits. Dental carries (76.6%, n = 70) and gum bleeding (14.9%, n = 14) were the most frequent reasons for visiting a dental clinic, and 73.7% (n = 70) had their tooth extracted. Barriers to seeking oral healthcare were cost of treatment (47.5%, n = 190), and long waiting time (18.5%, n = 74). The odds of seeking oral healthcare was 2.8-fold higher in participants who were being married (Odds ratio (OR): 2.8, 95% CI 1.3-6.3, p = 0.011) and 3.5-fold higher among housewives (COR: 3.5, 95% CI 1.1-11.4, p = 0.040). Conclusion About half of the participants had sought healthcare following a dental condition. Cost of treatment seems to be an important factor affecting utilization of oral health services. Optimization of costs, and creating awareness regarding benefits of utilizing preventive dental services are recommended.